Yogyakarta Is Special And The Culture Prove It / Djoko Dwiyanto, dkk.; editor, GBPH Yudaningrat,dkk. - Djoko Dwiyanto; Susilo; Much Guntari; GBPH Yudaningrat (Dinas Kebudayaan DIY, 2013)
Yogyakarta-Kebudayaanix, 182 hlm. ilus. 14 cm.